Extended-spectrum β-lactamase Producing Escherichia coli in Broiler Farms in Ciampea Bogor - Putra, Kenedy; Wahyuningsih, Wahyuningsih; Purwanti, Maya; Handayani, Kusuma Sri; Julaeha, Juju (ANIMAL PRODUCTION, 2025)
Long-term use of antibiotics in broiler chicken farming causes the emergence of resistant bacteria and increases the potential for multidrug-resistant bacteria. This study aims to investigate the presence and characteristics of extended-spectrum β-lactamase (ESBL) producing Escherichia coli (E. coli) in broiler farms located in Ciampea, Bogor. A total of 90 samples were taken from three broiler chicken farms located in Ciampea, Bogor. Sampling was carried out by swabbing the cloaca of 1% of the population on each farm. Gram staining and IMVIC biochemical tests were performed on colonies suspected of being E. coli. Confirmation of ESBL-producing E. coli using a double disc diffusion test with MHA. The results showed that ESBL-producing E. coli was present in 28,9% of broiler chicken cloaca swab samples (26/90). Antibiotic resistance tests of ESBL-producing E. coli isolates showed resistance to four antibiotics, namely chloramphenicol, amoxicillin, ciprofloxacin, and ampicillin. In this test, 22 isolates showed multidrug-resistant